2008
DOI: 10.1111/j.1468-2311.2008.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Science, Wrongful Convictions, and American Prosecutor Discretion

Abstract: A hot controversy exists about the reliability of forensic science as reported by prime-time drama television series in bringing violent criminals to justice. This exploratory research will show that neither forensics or its fictionalised (CSI Effect) accounts, nor substantial evidence secured by police investigators, shape prosecutor decisions to charge a suspect with a crime, which can often result in freeing guilty suspects and convicting innocent individuals. In the summer of 2006, 444 American prosecutors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…The fact that this phenomenon was present in those cases characterized by expressive homicide may reflect chronological change or cultural effect, as previous studies have connected forensic awareness to instrumental homicide (Salfati & Haratsis, 2001; Santtila et al, 2001; Santtila et al, 2008). As most offenders have become quite knowledgeable about forensic techniques to clean up forensic evidence left behind (Stevens, 2008), this may facilitate the commission of homicides when people use it as a last resort to deal with trivial conflicts that they experience in their daily lives (e.g., marital infidelity, arguments, collisions for money and love, quarrel or fight).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that this phenomenon was present in those cases characterized by expressive homicide may reflect chronological change or cultural effect, as previous studies have connected forensic awareness to instrumental homicide (Salfati & Haratsis, 2001; Santtila et al, 2001; Santtila et al, 2008). As most offenders have become quite knowledgeable about forensic techniques to clean up forensic evidence left behind (Stevens, 2008), this may facilitate the commission of homicides when people use it as a last resort to deal with trivial conflicts that they experience in their daily lives (e.g., marital infidelity, arguments, collisions for money and love, quarrel or fight).…”
Section: Discussionmentioning
confidence: 99%
“…While there is no certain way to know how many people have been wrongfully convicted in the United States, Risinger (2007) estimated that up to five percent of criminal convictions may occur when the individual is actually not guilty. Several systemic causes of wrongful conviction have been identified in the literature (Weathered, 2007), including faulty eyewitness testimony (Scheck, Neufeld, & Dwyer, 2000), false confessions and incriminating statements (Leo & Davis, 2010;Redlich, 2004), unreliable forensic science or forensic errors (Denov & Campbell, 2005), and personal bias or tunnel vision on the part of prosecutors (Stevens, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the majority of officers interviewed, there is a potential for public trust in the reliability of police forces to decrease due to unrealistic expectations created by CSI-type shows. This decrease in trust and reliance has been shown in the results of Stevens's (2008) study on the CSI effect and legal actors. It was found that police reports and non-forensic evidence collected by the police have had a reduced effect on guiding prosecution strategies in recent years.…”
Section: Police Officersmentioning
confidence: 56%